WAVELET BASED MULTICARRlER CODE DIVISION MUL TTPLE ACCESS COMMUNICATION FOR WIRELESS ENVIRONMENT - Hailemariam, Dereje (Zede Journal of Ethiopian Engineers and Architects, 2023)
ThIS paper presents the study on Wavelet transform based Mull/carrier Code D,VISIOn Multiple Access (MC-CDMA) system Jor a downlmk wlre/ess channel The performance of the .lystem IS slI/died for Additive While Gaussian Noise Channel (.4 WGN) and slowly varymg mulripafh channels. The bll error rale (BER) versus Signal to NOise ratIo (SNR) is Ilsed as a performance measure usmg Simulation done on compuler Comparison of the simulated results wilh the Iheoret/cal limit of a BPSK modulaled signal shows thai fhis system perJormsnear Ihe theoretical limit Jar both A WGN and slowly vQO'ing Flal fading channel. Also, a compal'lson with the Discrete Fourier Transform (DFJ) based system was made for A WGN channel and the result shows thai even In the absence of a guard Interval, the wavelet based system performs equally With (he DFr